An Observational Study to Compare the Effect of Two Different Doses of Dexmedetomidine on Hemodynamic Response to Laryngoscopy and Endotracheal Intubation (Medico Legal Update, 2021)
Background: Laryngoscopy and intubation are associated with intensesympathoadrenal stimulationresulting in hypertension, tachycardia & arrhythmias consequent to the release of catecholamines. Variousdrug regimens and techniques have been used from time to time for attenuating the stress response tolaryngoscopy and intubation, including opioids, barbiturates, benzodiazepines, beta blockers, calciumchannel blockers, vasodilators etc. Dexmedetomidine is a highly selective alpha 2 receptor agonist havingeight times higher affinity and alpha 2 selectivity compared to clonidine and has a shorter duration of actionthan clonidine.Material and Method: 60 patients scheduled for elective surgical procedures under general anaesthesiabelonging to ASA Grade I and II, in the age group of 18 to 60 years were divided into two study groups,D1 and D0.5 received dexmedetomidine 1 µg/kg and 0.5 µg/kg intravenously (iv) over 10 minutes beforeinduction. Hemodynamic responses were compared in both groups by measuring Heart rate (HR),Systolicblood pressure (SBP),Diastolic blood pressure(DBP),Mean arterial pressure (MAP) and SpO2 beforegiving the test drug (base line values),just before induction,during intubation and at 1 minute, 3 minutes, 5minutes,10 minutes after intubation. Statistical data were analyzed by using student’s unpaired t test.Observation and Results: Group D1 had 4.70% rise in HR and Group D0.5 had 9.59% rise during intubationwhich was statistically significant(p